1992
DOI: 10.1007/bf01238797
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited growth of common enteropathogenic bacteria in lactic-fermented cereal gruels

Abstract: A natural lactic fermentation of mixtures of water and whole flour of either maize or high-tannin sorghum was obtained either before or after cooking to a weaning gruel: The preparations had a final pH of about 3.8 (range 3.67 to 4.00) and a ratio of lactic acid to acetic acid of 9∶1 (w/w). The growth of added (about 10(7) c.f.u./g gruel) Gram-negative intestinal pathogenic bacteria, enterotoxigenicEscherichia coli, Campylobacter jejuni, Shigella flexneri andSalmonella typhimurium, was strongly inhibited in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 15 publications
3
26
1
2
Order By: Relevance
“…Similar results have been reported for other fermented products (Muyanja et al, 2003;Nout, 1991;Ruiz-Barba et al, 1994;Yan et al, 2008). Svanberg et al (1992) reported that lactic acid fermentation inhibited the proliferation of Gram-negative pathogenic bacteria including toxicogenic Escherichia coli, Campylobacter jejuni, Shigella flexneri and Salmonella typhimurium. Therefore, the decreased miscellaneous halotolerant bacteria obtained by inoculated fermentation may contribute to improve the quality of CHCP.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been reported for other fermented products (Muyanja et al, 2003;Nout, 1991;Ruiz-Barba et al, 1994;Yan et al, 2008). Svanberg et al (1992) reported that lactic acid fermentation inhibited the proliferation of Gram-negative pathogenic bacteria including toxicogenic Escherichia coli, Campylobacter jejuni, Shigella flexneri and Salmonella typhimurium. Therefore, the decreased miscellaneous halotolerant bacteria obtained by inoculated fermentation may contribute to improve the quality of CHCP.…”
Section: Resultsmentioning
confidence: 99%
“…The formation oflactic acid and acetic acid appears to be the reason for the inhibition of growth of Gram-negative intestinal pathogenic bacteria: such enterotoxigenic Escherichia coli, Campylobacter je juni, Shigella flexneria and S. typhimurium are strongly inhibited by the low pH [159]. In slight contrast, the inhibition of the Gram-positive Staphylococcus aureus is possibly due to the formation ofbacteriocins during the lactic acid fermentation as well as the effect of low pH [159]. Of considerable importance is the finding that all strains of a particular enteropathogenic bacterium appear to be equally susceptible to inhibition by lactic acid fermentation [160].…”
Section: Fermented Sorghum Porridgementioning
confidence: 99%
“…Lactic acid fermentation of sorghum porridge to a pH of 4.0 or below inhibits the growths of enterobacteriaceae, induding Salmonella typhimurium [158]. The formation oflactic acid and acetic acid appears to be the reason for the inhibition of growth of Gram-negative intestinal pathogenic bacteria: such enterotoxigenic Escherichia coli, Campylobacter je juni, Shigella flexneria and S. typhimurium are strongly inhibited by the low pH [159]. In slight contrast, the inhibition of the Gram-positive Staphylococcus aureus is possibly due to the formation ofbacteriocins during the lactic acid fermentation as well as the effect of low pH [159].…”
Section: Fermented Sorghum Porridgementioning
confidence: 99%
“…The results of all the samples confirmed that the detected colonies in the selective medium did not belong to Campylobacter spp. Svanberg et al (1992) and Svanberg (1996) reported that lactic acid-fermented gruels inhibited the proliferation of Gram-negative pathogenic bacteria including Campylobacter jejuni.…”
Section: Detection Of Campylobacter Sppmentioning
confidence: 99%
“…After the period of incubation, there were no bacteria growth (blue or blue green colonies) in all tested Karish samples. Svanberg et al (1992) and Svanberg (1996) reported that lactic acid-fermented gruels inhibited the proliferation of Gram-negative pathogenic bacteria including toxicogenic E. coli. The Egyptian Standard for Karish cheese (1008/4/200) recommended that the cheese should be free from E. coli.…”
Section: Escherichia Coli β-Glucuronidase Positivementioning
confidence: 99%